Diversity of Wild Mushrooms in Chaukot, Panauti - Jha, Sanjay Kumar; Thapa, Swostika (Perspectives on Higher Education, 2025)
Exploration on mushroom is relatively limited compared to other organism. This study aim to explore and documentation of diversity of wild mushrooms in chaukot community forest. A field survey was conducted in between 1500 and 1700 m a.s.l., to assess wild mushroom diversity. Mushrooms were sampled using quadrats along transects, identified through morphological and microscopic characteristics, and their diversity was evaluated using Shannon – wiener index and Simpson diversity index. A total of 68 mushroom were identified belonging Basidiomycota, Ascomycota and Mycetozoa. Among mushroom species, most of the mushroom were belongs to Russulaceae family and Agaricales order, Russula genera Laccaria laccata species in terms of number of species The highest species of mushroom were found in soil. More than half percentage of the mushroom were saprobe which favored by high canopy cover. Out of 68 species found in study area 34 mushroom species were edible, 19 inedible, 10 poisonous and 5 having unknown edibility. The current study showed Laccaria laccata had highest density and abundance. The Shannon diversity index was 3.78 and Simpson diversity index was 0.97 underscoring significant diversity. These findings emphasize the role of soil, and forest type in shaping mushroom diversity and their potential for ecological and local community applications.